"Spirituality": A Word that Everyone Uses and Some Believe that They Know What it Means. (24th February 2015) - Hunt, Stephen
Abstract : Legacy of the Founders: From Monks to Missionaries by Nicki Verpoegen. Lutterworth Press, 2012. 148pp. Pb. £15.25. ISBN-13: 97807188-92661. Subversive Spirituality: Transforming Mission Through the Collapse of Time by Paul L. Jenson. James Clarke, 2009. 392pp. Pb £22.00. ISBN-13: 9780227173572. Flights of the Soul: Visions, Heavenly Journeys and Peak Experiences in the Biblical World by John J. Pilch. William B. Eerdmans, 2011. 256pp. Pb. $24.00. ISBN-13: 9780802865403. Perceiving the Divine Body Through the Human Body: Mystical Sensuality by Thomas Cattoi and June McDaniel. Palgrave Macmillan, 2011. 264pp. Hb. $100.00. ISBN-13: 9780230119741. The Deepest Sense: A Cultural History of Touch by Constance Classen.University of Illinois Press, 2012. 256pp. Pb. $25.00. ISBN-13: 9780252078590; Hb. $80.00. ISBN-13: 9780252034930. The Hidden Spirituality of Men: Ten Metaphors to Awaken the Sacred Masculine by Matthew Fox. New World Library, 2008. 368pp. Pb. $16.95. ISBN-13: 9781577316756. Sanctifying Misandry: Goddess Ideology and the Fall of Man by Katherine, K. Young and Paul Nathanson. McGill-Queen's University Press, 2010. 424pp. Pb. CDN$34.95. ISBN-13: 9780773538733. Hb. CDN$95.00. ISBN-13: 9780773536159.